First Medical Contact-to-Device Time and Heart Failure Outcomes Among Patients Undergoing Primary Percutaneous Coronary Intervention. Issue 8 (August 2018) - Loh, Joshua P; Tan, Li-Ling; Zheng, Huili; Lau, Yee-How; Chan, Siew-Pang; Tan, Kelvin-Bryan; Chua, Terrance; Tan, Huay-Cheem; Foo, David; Lee, Chee-Wan; Tong, Khim-Leng; Foo, Ling-Li; et al.
Abstract : Background: Expediting reperfusion during primary percutaneous coronary intervention is aimed at salvaging myocardium in ST-segment–elevation myocardial infarction. Few studies have examined the relation between reperfusion time and heart failure (HF) events. Methods and Results: We studied 7597 patients undergoing primary percutaneous coronary intervention from 2007 to 2013 in the Singapore Myocardial Infarct Registry, which captures HF at admission, postadmission in-hospital HF, and HF rehospitalization. We studied the relation of first medical contact to deployment of first device to achieve reperfusion (FTD) time with in-hospital HF events and HF rehospitalization, with mortality modeled as a competing risk. At the population level, median FTD time decreased from 91 minutes (interquartile range, 69–114) in 2007 to 58 minutes (45–75) in 2013 ( P =0.001), whereas mortality remained unchanged (in-hospital: range 5.3%–7.3%; P =0.190 and 1-year: range 7.8%–10.9%; P =0.505). HF at admission increased from 12.2% in 2007 to 18.4% in 2013, P =0.020, whereas postadmission in-hospital HF decreased from 12.8% in 2007 to 7.1% in 2013, P =0.030. HF rehospitalization increased from 1.2% in 2007 to 2.6% in 2013 ( P =0.003), for 30-day HF rehospitalization, and 3.8% in 2007 to 5.6% in 2013 ( P =0.037), for 1-year HF rehospitalization. At the individual level, among patients with HF at admission (N=1191), longer FTD time was associated with more 30-day HF rehospitalization (compared with ⩽60 minutes, adjusted hazard ratio, 1.68 [0.73–3.86] for 60–90 minutes, 2.88 [1.19–6.92], for 90–120 minutes, and 2.84 [1.08–7.44] for >120 minutes). Longer FTD time was associated with a greater risk of postadmission in-hospital HF (compared with ⩽60 minutes, adjusted hazard ratio, 1.18 [0.96–1.44] for 60–90 minutes, 1.59 [1.25–2.03] for 90–120 minutes, and 1.67 [1.26–2.21] for >120 minutes). Conclusions: Temporal reductions in FTD time were associated with decrease in postadmission in-hospital HF. Among patients presenting with HF at admission, delays in FTD beyond 90 minutes were associated with more 30-day HF rehospitalization. Abstract : Supplemental Digital Content is available in the text.